Epigenetic repolarization of T lymphocytes from chronic lymphocytic leukemia patients using 5-aza-2′-deoxycytidine - Dubovsky, Jason A. (Leuk Res, 2011)
T cell immune dysfunction has an important role in the profound immunosupression that characterizes chronic lymphocytic leukemia (CLL). Improper polarization of T cells has been proposed as one of the mechanism involved. Mounting data implicates chromatin regulation, namely promoter methylation, in the plasticity of naïve human T cells. Recent in vitro evidence indicates that this plasticity may be phenotypically altered by using methylation inhibitors which are approved for clinical use in certain types of cancer. These results beg the question: can the ineffective polarization of T lymphocytes in the context of CLL be effectively modulated using methylation inhibitors in a sustainable therapeutic fashion? To answer this question our laboratory has studied the effects of 5-aza-2′-deoxycytidine (5A2) in helper and cytotoxic T lymphocytes from healthy donors and CLL patients in well characterized molecular and epigenetic signaling pathways involved in effective polarization. Moreover, we sought to investigate the consequences of methylation inhibitor treatment on lymphocyte survival, activation intensity, and naïve cell polarization. Our data indicates that 5A2 treatment can repolarize Th2 cells to effectively secrete interferon gamma, signal via T-bet, and achieve demethylation of critical Th1 specific promoters. Moreover, we demonstrate that 5A2 can force Th1 polarization of naïve T cells despite a strong IL-4 stimuli and a lack of IL-12. In conclusion our data seeks to define a modality in which improper or ineffective T cell polarization can be altered by 5AZA and could be incorporated in future therapeutic interventions.